Regras e poder: uma análise das contingências descritas no código de ética e disciplina dos militares capixabas - Oliveira, Leticia Garcia de (2023)
This is a documental study guided by behavior analysis theoretical framework which uses the three-term contingency as the central unit of analysis. The objective of this research was to identify and describe the contingencies present in the rules comprising the new Code of Ethics and Discipline of Espírito Santo State Military and, subsequently, reflect on possible implications of these regulations considering: (a) their function in controlling the behavior of police officers; (b) their function for the institution of Miliary Police; and (c) their function for the civil society. To this end, the components of the contingencies were identified, described and subsequently analyzed by four judges regarding the objective of the very existence of the rule, considering its effects beyond the manifest function of controlling behavior. By “effects” we mean not the explicit function of controlling the behavior of the police officers, but their “purpose”: Whom does it serve? In other words, the goal was to try to understand about “who” one was thinking when building those rules and “why” they were created.